PENGEMBANGAN E – LKPD BERBASIS PENDEKATAN SOCIO-SCIENTIFIC ISSUE KONTEKS MANGROVE TERINTEGRASI SOAL TES BERPIKIR KRITIS - Wulandari, Sri; Putera, Dwi Bagus Rendy Astid; Tamam, Badrud; Fikriyah, Aida; Wahyudhi, Sunu (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
The development of electronic student worksheets is one of the electronic-based teaching materials. This study was conducted with the aim of determining the validity and student responses to electronic student worksheets based on the socio-scientific issue approach in the mangrove context. This type of research is R&D with the ADDIE development model. The main focus of this study is on the implementation stage, which aims to test the feasibility and effectiveness of the learning media that has been developed. The subjects in this study were class VII-C students of SMPN 4 Kamal. The data analysis techniques were validity analysis and student response analysis. Based on the results of the study, it can be concluded that: (1) The average validity of media experts is 93.75% with very valid criteria, while the average validity of material experts is 93.75% with very valid criteria (2) The average student response results to electronic student worksheets teaching materials based on the socio-scientific issue approach in the mangrove context are 91.82% with very good criteria. This shows that electronic student worksheets teaching materials based on the socio-scientific issue approach in the mangrove context are suitable for use in learning.Kata kunci: E – LKPD, mangrove, Socio-scientific issue